Design and Development of Project-Based English Learning Modules for Senior High School 1 Hiliduho - Cinta mendrofa; Alfina Mendrofa; Arni Mendrofa; Cinthika Harefa; Florencia Gulo; Irawan Gea; Maria Halawa; Yaredi Waruwu (Edu-Ling: Journal of English Education and Linguistics, 2025)
This research aimed to design and develop project-based English learning modules (PBL) for SMA Negeri 1 Hiliduho. The study used the Research and Development (R&D) method, based on a simplified Borg and Gall model consisting of four stages: data collection, module design, development and validation, and limited implementation. Data were gathered through interviews, observations, and questionnaires, and analyzed using pre- and post-tests, as well as teacher and student feedback. The findings showed that the modules effectively enhanced students' English proficiency, particularly in speaking and writing skills, with an average score increase of 20%. Additionally, 85% of students and 90% of teachers provided positive feedback on the modules. This study contributed to the implementation of project-based learning in English as a Foreign Language (EFL) contexts, particularly in rural Indonesian high schools.